NADPH Oxidase Regulates the Growth and Pathogenicity of Penicillium expansum - Zhang, Xuemei; Zong, Yuanyuan; Gong, Di; Yu, Lirong; Sionov, Edward; Bi, Yang; Prusky, Dov (Frontiers in Plant Science, 2021)
The occurrence of reactive oxygen species (ROS) during the colonization of necrotrophic pathogens attacking fruit is critical during the attack, but its importance in Penicillium expansum remains unclear. This study aimed to determine the regulatory effects of NADPH oxidase (Nox) genes on the growth and pathogenicity of P. expansum in apple fruits. Deletion mutants of ΔPeNoxA, ΔPeNoxR, and ΔPeRacA genes were constructed to determine the contribution to the colonization process. The ΔPeRacA strain had a significant effect on the reduction of growth and pathogenicity, the ΔPeNoxA strain negatively regulated the growth and development of P. expansum and did not show any significant effect on the pathogenicity, and the ΔPeNoxR strain showed no effect on the growth or pathogenicity of P. expansum in the apple fruits. However, analysis of the content of O2– and H2O2 in the mycelium of all the Nox mutants showed a significant reduction, confirming the functionality of Nox mutations. Growth under stress conditions in the presence of Congo red, sodium lauryl sulfate, and H2O2 showed a negative effect on the radial growth of ΔPeNoxA, but a positive effect on radial growth reduction by ΔPeNoxR and ΔPeRacA mutants was shown. Interestingly, the host antioxidant activity levels of superoxide dismutase (SOD) andcatalase (CAT) in the fruits after inoculation with ΔPeNoxA, ΔPeNoxR, and ΔPeRacA mutants declined, suggesting reduced ROS accumulation in the colonized region. These results suggest that PeNoxA, PeNoxR, and PeRacA differentially regulate the growth and pathogenicity of P. expansum by producing ROS, and that PeRacA showed the strongest regulatory effect.